USE OF ACCOUNTING DATA IN NATIONAL-INCOME ESTIMATION. - Nelson, Carl L. (The Accounting Review, 1953)
Abstract Accountants have long been accustomed to the multiple use of accounting data presented in the annual statements issued by American business firms. These statements were originally prepared primarily for the management, and secondarily for the banker. The accountant has long realized the problems raised by the multiple use of accounting data because the information needed by one group may be different than that needed by a second. As a result of these confusing situations, some accountants have favored the use of single-purpose statements. Accountants must now realize that the results of their efforts are used for purposes that may be entirely foreign to the internal affairs of the particular business organization. Most widespread of these at the present time is the combination of the accounting figures reported by each of the firms in the U.S. in the national income estimates by the Department of Commerce. This work has been done by statisticians and economists rather than by accountants, but the accounting profession should be grateful to the intelligent way that these groups have used the product of accounting.